Sarungan Sexology: Exploring the Moral Ideas of the Qurán as an Effort to Prevent Sexual Violence in Pesantren - Rifqi As'adah Laili; Ubaidillah Hasan; Siti Marpuah (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2025)
Sexual violence at public educational institutions, particularly Pesantren or Islamic Boarding Schools, is a strong warning since it has gone beyond the limits of public values, morality, and ethics, even in sacred spaces. This study investigates how the Qur'an and pesantren sexology literature respond to violence through a thematic examination of Qur'anic verses and analysis of pesantren literature material using a linguistic structural analysis approach. As a result, key phrases like al-'Aurat, Tasta'nisu, Ghaddu al-Bashar, 'Adam al Ikhtilat, Zinatun, al-Farj, Tukhalitu, and Fakhisyah are included in the Qur'anic moral concept of language structure. When considered in its context, the phrase demonstrates value in two significant ways: first, it highlights the relationship between Kiyai and Santri, which is followed by the paradigm of sexology preventative literacy for teenagers, and second, it highlights the preventive system of pesantren spatial management and the communication model.